Evaluasi Afektif dalam Pembelajaran - Purnama Rozak (Sekolah Tinggi Ilmu Tarbiyah (STIT) Pemalang, 2014)
In the taxonomy of Benjamin S. Bloom there are three domains of education, namely the realm of thinking (cognitive domain), the realm of values ​​or attitudes (affective domain), and the realm of skills (psychomotor domain). These three domains of education are the objectives of education in Indonesia, as stated in the Republic of Indonesia Law number 20 of 2003 concerning the national education system to develop the potential of students to become people of faith, and devote to God Almighty, noble, healthy, knowledgeable, capable, creative, independent, and become democratic and responsible citizens, so we can conclude that the cognitive domain is knowledge. The affective domains are faithful and pious, noble, independent, democratic, responsible. The psychomotor domain is healthy, capable, creative. These three areas must be targeted in every learning evaluation activity. In measuring the learning outcomes of affective areas, including difficult because it involves areas of attitude and appreciation. Affective evaluation deals with the formation and change of attitude.